Liposome-mediated macrophage reprogramming: emerging strategies for chronic disease therapy - Zhang, Hongnv; Hu, Nan; Wang, Zhenghao; Zhai, Shaodong (Frontiers in Immunology, 2025)
With the rapid advancement of nanotechnology, the application of nanomedicine has become increasingly widespread, demonstrating remarkable potential for highly precise targeting and efficacious drug delivery. Compared to conventional drug delivery approaches, nanomedicine effectively addresses issues such as nonspecific drug distribution and severe adverse effects, significantly enhancing therapeutic efficacy through its targeted delivery mechanisms. As an innovative drug delivery vehicle, liposomes exhibit tremendous application potential owing to their outstanding biocompatibility, extensive applicability, remarkable ability to improve drug stability and bioavailability, precise targeting capabilities, membrane structures that facilitate drug permeation, and high degree of tunability. In the field of chronic disease management, liposomes serve as sophisticated vehicles for targeted and controlled drug delivery, offering innovative therapeutic approaches for various chronic conditions. Macrophages, which play a pivotal role in modulating inflammatory responses and promoting tissue repair, have emerged as crucial targets for alleviating inflammatory symptoms. Nevertheless, achieving precise and efficient targeting of macrophages remains a significant challenge in current research. This article systematically reviews recent advances in liposome-based therapies for chronic diseases, including cardiovascular diseases, cancers, chronic respiratory diseases (e.g., chronic obstructive pulmonary disease, pulmonary fibrosis, and asthma), and metabolic disorders (e.g., diabetes), with particular emphasis on the therapeutic potential of liposomes in modulating macrophage activity. Furthermore, it summarizes and analyzes the major challenges and obstacles currently faced in liposome research, providing novel insights for future research directions and facilitating the translation of research findings into clinical applications.